DEFINITIONS PEDAGOGICAL TESTING - Сілакова, Т. Т. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In this paper the authors is given a detailed definition of the concept of integration of pedagogical testing. This definition is decomposed into separate components, characterizing testing as a method of educational measurement of educational achievements of students. We considered in detail each of the components of pedagogical testing, starting with the formulation of test questions and to organizing the testing process. Attention is drawn to the need for compliance with the methodology of systematic approach at all stages of preparation and implementation of the tests. Particular attention is paid to the definition of the characteristics that affect the test results, providing the ability to most effectively use the information obtained as a result of its implementation